A single, low dose of a cGMP recombinant BCG vaccine elicits protective T cell immunity against the human respiratory syncytial virus infection and prevents lung pathology in mice. Issue 5 (1st February 2017) - Céspedes, Pablo F.; Rey-Jurado, Emma; Espinoza, Janyra A.; Rivera, Claudia A.; Canedo-Marroquín, Gisela; Bueno, Susan M.; Kalergis, Alexis M.
Highlights: A single dose of 3 × 10 5 CFUs of rBCG-N-hRSV cGMP elicits T-cell memory against hRSV. rBCG-N-hRSV cGMP elicits a strong antiviral TH1/TH17 T-cell repertoire. Vaccination prevents viral pneumonia and CNS-alterations associated with hRSV. rBCG-N-hRSV cGMP elicits a strong anti-mycobacterial TH1/TH17 T-cell repertoire. Immunity to hRSV and Mtb antigens develops without observable adverse effects. Abstract: Human respiratory syncytial virus (hRSV) is a major health burden worldwide, causing the majority of hospitalizations in children under two years old due to bronchiolitis and pneumonia. HRSV causes year-to-year outbreaks of disease, which also affects the elderly and immunocompromised adults. Furthermore, both hRSV morbidity and epidemics are explained by a consistently high rate of re-infections that take place throughout the patient life. Although significant efforts have been invested worldwide, currently there are no licensed vaccines to prevent hRSV infection. Here, we describe that a recombinant Bacillus Calmette-Guerin (BCG) vaccine expressing the nucleoprotein (N) of hRSV formulated under current good manufacture practices (cGMP rBCG-N-hRSV) confers protective immunity to the virus in mice. Our results show that a single dose of the GMP rBCG-N-hRSV vaccine retains its capacity to protect mice against a challenge with a disease-causing infection of 1 × 10 7 plaque-forming units (PFUs) of the hRSV A2 clinical strain 13018-8. Compared to unimmunized infected controls, vaccinated mice displayed reduced weight loss and less infiltration of neutrophils within the airways, as well as reduced viral loads in bronchoalveolar lavages, parameters that are characteristic of hRSV infection in mice. Also, ex vivo re-stimulation of splenic T cells at 28 days post-immunization activated a repertoire of T cells secreting IFN-γ and IL-17, which further suggest that the rBCG-N-hRSV vaccine induced a mixed, CD8 + and CD4 + T cell response capable of both restraining viral spread and preventing damage of the lungs. All these features support the notion that rBCG-N-hRSV is a promising candidate vaccine to be used in humans to prevent the disease caused by hRSV in the susceptible population.